Narrative attributions of entrepreneurial failure - Mantere, Saku; Aula, Pekka; Schildt, Henri; Vaara, Eero (Journal of Business Venturing, 2013)
We examine how organizational stakeholders use narratives in their psychological processing of venture failure. We identify a range of “narrative attributions”, alternative accounts of failure that actors draw on to process the failure and their role in it. Our analysis provides a view of entrepreneurial failure as a complex social construction, as entrepreneurs, hired executives, employees and the media construct failure in distinctively different ways. Narratives provide means for both cognitive and emotional processing of failure through grief recovery and self-justification.